Очищення поверхонь нагріву регенеративних повітропідігрівників перед їх консервацією - Мисак, Йосиф; Янко, Петро; Івасик, Ярослав; Якимів, Євген (Видавництво Національного університету «Львівська політехніка», 2001)
In this work we propose the technology of the first stage conservation of the regenerative’s air-conducting in time the stand powers bloks by means clearing from it’s put’s off.